Substantia : media studi dan keagamaan - Institut Agama Islam Negeri Jamiʼah ar-Raniry. Fakultas Ushuluddin
Journal on study and researches on Islam in Indonesia.
Keywords: Islam : Study and teaching : Indonesia : Periodicals; Islam : Indonesia : Periodicals; Islam; Islam : Study and teaching; Indonesia